The synthesis and complexation study of some coumestan and coumestan analog derivatives of crown ethers using conductometry - (:unkn) unknown (ELSEVIER SCI LTD, 2005)
8,9-Dihydroxycoumestans, the 8,9-dihydroxy-6H-benzofuro[3,2-c][1]-benzopyran-6-one, derivatives were prepared from corresponding 4-hydroxy-2H-[1]benzopyran-2-one and catechol in oxidizing mixture KIO3/CH3COONa/H2O/acetone while for the oxidative coupling of cyclohexane-1,3-dione and catechol, K-3[Fe(CN)(6)]/CH3COONa/H2O/aectone was used. The derivatives of 8,9-dihydroxycoumestan and 8,9-dihydroxy-1,4-dimethy-6H-benzofuro[3,2-c][1]-benzopyran-6-one and two coumestan analog compounds reacted with the bis-dihalides of polyglycols in CH3CN/Me2CO3 to furnish coumestano-12-Crown-4, 15-Crown-5 and 18-Crown-6. The crude products were purified using silica gel chromatography with chloroform. The obtained novel pure crown ethers were identified with IR, H-1 NMR, C-13 NMR, mass spectroscopy and elemental analysis. Formation constants for complexation between NaClO4 and the various coumestano-crown ethers in the solvent acetonitrile at 25degreesC were determined from conductance measurements. The method also permits accurate evaluation of association equilibrium constants between the complex species (M-Coumestano-crown ether)(+) and the anion. The magnitudes of these ion association constants are related to the nature of the solvation of the cation and of the complexed cation. Structures of crown compound-cation complexes in acetonitrile are estimated from the conductance parameters (K. 21 and a) as well as complex formation constant {K-e = (Lambda(MAm), - Lambda)/((Lambda - Lambda(MLAm))[L])}. The complexation study indicates 1:1 complex formation between the metal ion and the crown ether. All the experimental studies have been conducted using the ratio 1:1 of the metal ion and the crown ether. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: coumestano-crown ethers; synthesis; complexation; conductometry; ION-SELECTIVE ELECTRODES; MACROCYCLIC POLYETHERS; EQUILIBRIUM-CONSTANTS; DIOXANE-WATER; METAL SALTS; CONDUCTANCE; CHEMISTRY; BEHAVIOR; CATIONS; ALKALI